2014
DOI: 10.1117/1.jmi.1.2.025001
|View full text |Cite
|
Sign up to set email alerts
|

In vivo reproducibility of robotic probe placement for a novel ultrasound-guided radiation therapy system

Abstract: Abstract. Ultrasound can provide real-time image guidance of radiation therapy, but the probe-induced tissue deformations cause local deviations from the treatment plan. If placed during treatment planning, the probe causes streak artifacts in required computed tomography (CT) images. To overcome these challenges, we propose robot-assisted placement of an ultrasound probe, followed by replacement with a geometrically identical, CT-compatible model probe. In vivo reproducibility was investigated by implanting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…The workflow is separated into a planning day, where the planning images of the patient are acquired, and multiple (fractionated) treatment days, where the radiation therapy is delivered. A more detailed discussion of this workflow can be found in Bell et al (2014) and Sen et al (2015). In this section, we focus on the use of cooperative control within this workflow.…”
Section: Cooperative Control In the Radiotherapy Workflowmentioning
confidence: 99%
See 1 more Smart Citation
“…The workflow is separated into a planning day, where the planning images of the patient are acquired, and multiple (fractionated) treatment days, where the radiation therapy is delivered. A more detailed discussion of this workflow can be found in Bell et al (2014) and Sen et al (2015). In this section, we focus on the use of cooperative control within this workflow.…”
Section: Cooperative Control In the Radiotherapy Workflowmentioning
confidence: 99%
“…A phantom study is performed to demonstrate that this strategy enables an operator to quickly and accurately reproduce a reference US image. As the phantom does not exhibit realistic soft-tissue deformation, an illustration of this phenomenon can be found in the in vivo canine study reported in Bell et al (2014). Much of the material presented in this paper is based on the dissertation by Sen (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, two major deficiencies have become apparent when CBCT is applied to verify radiotherapy: (1) CBCT only provides a snapshot of patient information at the time of imaging, but not during actual radiation delivery, and (2) CBCT often does not provide sufficient contrast to discriminate soft tissue targets. US imaging can overcome these deficiencies as in [1]–[3], but the ionizing radiation precludes an ultrasonographer from holding the US probe on the patient during treatment. This has motivated the development of passive probe holders [4] and at least one telerobotic system [5], [6] for US monitoring during radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Lediju et al extended the use of a robotic US probe for lower abdomen in an animal study and reported that the average 3D reproducibility of their robotic US probe was less than 2 mm [17]. Moreover, the feasibility of implementing US imaging into liver SBRT for eleven patients was shown by Gurp [18].…”
Section: Fargier Et Al Compared the Inter-observer Variations Of Tramentioning
confidence: 99%